Effects of synthetic 2, 4, 6-trihydroxy-3-geranylacetophenone upon TNF-α-induced epithelial dysfunction - Sim, Tee Yee (2016)
Asthma is characterized by activation of Th-2 (T-helper-2)-type T-cell, and patients clinically presented with breathlessness, wheezing, cough, and chest tightness. Current treatments for asthma is just symptomatic relieve during acute exacerbation and prevent from attacks using controllers. All this treatment is not actually treating the new pathogenesis of this disease which is targeting the airway epithelium barrier. Studies shown 5-10% of asthma patient does not have any responds towards usual corticosteroid treatment, therefore there is a need to develop a new drug which can work on the actual pathogenesis of asthma. Airway epithelium plays a critical role in inflammatory reactions by acting as a barrier to external environment, producing chemokines and expressing cell-surface adhesion molecules for recruitment of effector cells. Preliminary studies show that 2,4,6–trihydroxy–3– geranylacetophenone (tHGA) inhibits the synthesis of cysteinyl leukotrienes in activated macrophages via inhibition of 5-lipoxygenase (5-LO) enzymatic activity. This study aimed to determine inhibitory effect of tHGA on adhesion molecule, epithelium hyperpermeability, tight junction barrier and pro-inflammatory signaling pathways that are involved. A549 cell was induced with tumor necrosis factor alpha (TNF-α) 10ng/mL and co-treated with different concentration of tHGA (50μM, 12μM, 3μM) and Dexamethsone 10 μM act as drug control group. Epithelium hyperpermeability was measured by fluorescein isothiocyanate–dextran (FITC-Dextran) permeability assay and trans-epithelial electrical resistance (TEER). Adhesion assay and transepithelium migration assay was performed by using A549 cells and U937 cells. Enzyme-linked immunosorbent assay (ELISA) was used to determine soluble intercellular adhesion molecule-1 (sICAM-1) level and monocyte chemoattractant protein-1 (MCP-1) levels. Membrane expression of tight junction complexes proteins (Zonula occluden 1, occludin, and E-cadherin) was investigated under immunofluorescence, gene expression and protein expression studies. Phosphorylation of mitogen-activated protein kinases (MAPK) and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) pathway was studied. The data obtained concluded that 50 μM tHGA had 32.10 ± 8.03% significantly suppressed leukocytes moving across epithelium. tHGA had reduced adhesion molecule expression by 43.45 ± 0.16%, therefore inhibit adhesion of monocytes to tumor necrosis factor TNF-α induced epithelium (43 ± 5.77%) and reduce transepithelium migration. tHGA is able to increase TEER, reduce epithelium hyperpermeability by 41± 6.35%. tHGA enhance airway barrier integrity through redistribution of TJ proteins (ZO-1, occludin) and AJ protein (E-cadherin) and NF-κB pathway and MAPK pathway be could involved in this process.